Formulaic language. (5th June 2013) - Wray, Alison
Abstract : Creating a timeline for formulaic language is far from simple, because several partially independent lines of research have contributed to the emerging picture. Each exhibits cycles of innovation and consolidation over time: domains take a leading role in developing new knowledge and then fall back, while another area comes to the fore. Thus, some of the first observations about formulaic language, back in the nineteenth century, were in the clinical domain of aphasia studies. By the early to mid twentieth century it was theories of language structure that had most to say, until eclipsed by the Chomskian model, which saw little significance in lexicalised units larger than the word (an issue discussed by Jackendoff2002 ; see table entry). Meanwhile, changes in language teaching methodology in the mid to late twentieth century increasingly urged teachers to ask how adult learners could best master multiword strings to improve fluency and idiomaticity – a question still asked today. By the end of the twentieth century, new technological advances revealed frequency in usage as a probable agent of formulaicity, and these chimed with new models of lexical knowledge based on neural pathways and networks that could be strengthened by repeated exposure. Drawing on these models, we have seen, as we move into the twenty-first century, the development of new approaches to modelling language as a system – emergent grammars, including Construction Grammar – that are more accommodating of large, internally complex units. And finally, as we gradually understand more about how the brain accesses and retrieves linguistic material, we are seeing a resurgence of interest in formulaic language in neurological and clinical contexts.